2016
DOI: 10.1016/j.marpolbul.2016.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Status of POPs accumulation in the Yellow River Delta: From distribution to risk assessment

Abstract: The Yellow River Delta (YRD) is a large region of China with complex pollution sources and a long history of environmental deterioration. Despite this, relatively little data exists on the status of important contaminants of concern in this region. Here, we review the literature on the status of key persistent organic pollutants (POPs) of concern including organochlorine pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs), and polychlorinated biphenyls (PCBs) in the YRD. Sources, source identification m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In this study the highest % proportion of HCHs was contributed by β-HCH (68.18%) followed by α-HCH (18.26%), and γ-HCH (10.97%). β-HCH is known for its high persistence and poor biodegradability in soil and sediment [ 57 59 ] and these properties might have contributed for its abundance in the river sediments of the Awash River Basin. [ 58 ] reported that α-HCH and γ-HCH can be biodegraded to β-HCH in the natural environment.…”
Section: Resultsmentioning
confidence: 99%
“…In this study the highest % proportion of HCHs was contributed by β-HCH (68.18%) followed by α-HCH (18.26%), and γ-HCH (10.97%). β-HCH is known for its high persistence and poor biodegradability in soil and sediment [ 57 59 ] and these properties might have contributed for its abundance in the river sediments of the Awash River Basin. [ 58 ] reported that α-HCH and γ-HCH can be biodegraded to β-HCH in the natural environment.…”
Section: Resultsmentioning
confidence: 99%
“…The present study involved a large-scale investigation of the temporal and spatial distributions of CUPs in surface seawater and atmosphere. Previous studies have focused mainly on CUPs at specific regions or locations (Eickmeyer et al, 2016;Li et al, 2016;Ruggirello et al, 2010;Yeo et al, 2004), with few having largescale profiles (Ma et al, 2015). Zhong, Xie, Cai, et al (2012) studied CUPs during the 4th Chinese National Arctic Research Expedition (CHINARE) in a similar region of the North Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The target compounds are expected to discharge into the Bohai Sea through the runoff of the Yellow and Haihe Rivers (Fig. 1), which are among the seven largest water systems in China, and receive large volumes of industrial or agricultural wastewater leading to serious pollution levels (Li et al, 2013;Li et al, 2016). For example, the Yellow River flows through Zibo City, which is the largest production base of Chlorpyrifos in Northern China (15,000 t/y), this may explain the high concentration of Chlorpyrifos in SW6 and SW7.…”
Section: Cups In Seawatermentioning
confidence: 99%